RESPITE: switching to riociguat in pulmonary arterial hypertension patients with inadequate response to phosphodiesterase-5 inhibitors. Issue 3 (9th September 2017) - Hoeper, Marius M.; Simonneau, Gérald; Corris, Paul A.; Ghofrani, Hossein-Ardeschir; Klinger, James R.; Langleben, David; Naeije, Robert; Jansa, Pavel; Rosenkranz, Stephan; Scelsi, Laura; Grünig, Ekkehard; Vizza, Carmine Dario; et al.
A proportion of pulmonary arterial hypertension (PAH) patients do not reach treatment goals with phosphodiesterase-5 inhibitors (PDE5i). RESPITE investigated the safety, feasibility and benefit of switching from PDE5i to riociguat in these patients. RESPITE was a 24-week, open-label, multicentre, uncontrolled study. Patients in World Health Organization (WHO) functional class (FC) III, with 6-min walking distance (6MWD) 165–440 m, cardiac index <3.0 L·min −1 ·m −2 and pulmonary vascular resistance >400 dyn·s·cm −5 underwent a 1–3 day PDE5i treatment-free period before receiving riociguat adjusted up to 2.5 mg maximum t.i.d . Exploratory end-points included change in 6MWD, WHO FC, N -terminal prohormone of brain natriuretic peptide (NT-proBNP) and safety. Of 61 patients enrolled, 51 (84%) completed RESPITE. 50 (82%) were receiving concomitant endothelin receptor antagonists. At week 24, mean±sd 6MWD had increased by 31±63 m, NT-proBNP decreased by 347±1235 pg·mL −1 and WHO FC improved in 28 patients (54%). 32 patients (52%) experienced study drug-related adverse events and 10 (16%) experienced serious adverse events (2 (3%) study drug-related, none during the PDE5i treatment-free period). Six patients (10%) experienced clinical worsening, including death in two (not study drug-related). In conclusion, selected patients with PAH may benefit from switching from PDE5i to riociguat, but this strategy needs to be further studied. Switching to riociguat in PAH patients with inadequate response to PDE5i improved exercise capacity and NT-proBNP http://ow.ly/e6xL30dXCgy